2017
DOI: 10.1111/jonm.12501
|View full text |Cite
|
Sign up to set email alerts
|

Using social media to engage nurses in health policy development

Abstract: Aims:To explore nurses' views on future priorities for the profession and to examine social media as an engagement tool to aid policy discussion and development.Background: Nurses are often not directly involved in policy creation and some feel it is a process they cannot easily influence. Methods:A descriptive mixed methods study of a Twitter chat hosted by the Chief Nursing Officer for Scotland was undertaken. Data were gathered using an analytics platform and NCapture software. The framework approach aided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 30 publications
0
51
0
1
Order By: Relevance
“…Nurses across all settings should also work for improving the image of nursing and confronting the dominance of physicians at policy forums. To achieve this, nurses can participate in policy debates and discussions over social media (O'Connor, 2017), and take initiatives and avail themselves of opportunities to participate in institutional policy making and participate confidently at the policy forums. Nurse leaders could lobby other nurse representatives at the policy forums (Shariff, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Nurses across all settings should also work for improving the image of nursing and confronting the dominance of physicians at policy forums. To achieve this, nurses can participate in policy debates and discussions over social media (O'Connor, 2017), and take initiatives and avail themselves of opportunities to participate in institutional policy making and participate confidently at the policy forums. Nurse leaders could lobby other nurse representatives at the policy forums (Shariff, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Parallel to our study, the study of O'connor (29) showed that education and research are necessary to develop nursing workforces' participation.…”
Section: Conceptual Frameworkmentioning
confidence: 61%
“…Nurses in leadership roles, especially those leading professional organizations, are well prepared and positioned to develop policy ideas, set professional standards, and advocate for health policies (Burton et al., ) that improve access to high‐quality nursing and healthcare services. While more research on why and how nurses use social media is needed (O'Connor, ), organizations and individuals deciding to explicitly share policy‐relevant content in the weeks preceding elections could be a strategy to keep health and health policy at the forefront of democratic decisions. To that end, leaders of professional nursing organizations—and nurses and leaders in practice and academics—should consider how social media communications could be better used to build support for health policy ideas and priorities, and for the nursing profession.…”
Section: Discussionmentioning
confidence: 99%